EFFECTIVENESS OF CLASSROOM ACTION RESEARCH TRAINING FOR PRIMARY SCHOOL TEACHER IN ORDER TO IMPROVE THE CAPABILITY AND PROFESSIONALISM OF TEACHER AT SDN 04 IX KORONG SOLOK CITY - Afrahamiryano Afrahamiryano (STKIP Singkawang, 2017)
Training of Classroom Action Research is an effort to increase the understanding and skills of teachers in preparing the research proposal, conducting research, as well as a research report. This training is subject teachers at SDN 04 IX Korong totaling 19 people. The training was conducted by the lecture method which collaborated with guided exercises. The use of this method is effective to increase the interest of teachers in writing, because every teacher guided continuous and programmed. This training provides a positive impact for teachers at SDN 04 Korong IX. It is seen from the 19 teachers who attended the training, there are 11 teachers who successfully complete the Class Action Research to stage the final report. It shows that 57.9% of teachers at SDN 04 IX Korong able to do research and have a high enough motivation to produce the scientific work. So based on this study, it can be concluded that the training of classroom action research which is continuous and effective programmed to build capabilities and professionalism of teachers.